La recaudación de impuestos municipales y el desarrollo sostenible del Distrito de Contamana, 2023 - Campos Avila, Alex (2024)
The objective of this report was to determine the relationship between the collection of municipal taxes and the sustainable development of the district of Contamana, 2023, where an applied type study, descriptive-correlational level and non-experimental design was chosen, selecting a sample of 329 taxpayers, to whom a questionnaire was used to collect information. According to the results obtained, the level of municipal tax collection is regular (34%), because the Municipal Tax Administration service sometimes educates about tax culture; Like, actions have almost always been implemented so that the user pays the total amount of their debt. For its part, the level of sustainable development is regular (32%) since it can rarely be reduced by paying property taxes; as well as the timely payment of their taxes, since it rarely improves the services provided by the municipality; but they agree with the municipality, since it almost always exercises ecological policies to avoid environmental pollution in its district. Managing to determine that there is a significant relationship between the variables, which was corroborated by a Rho coefficient (0.629) and a bilateral significance of 0.000.